Investigation of the Clinical and Diffusion-Weighted Brain Magnetic Resonance Imaging Findings in the Patients with Repeated Transient Stereotypical Neurological Deficit in Loghman-Hakim Hospital from 2019 to 2020 - Zoghi, Anahita; Shahidi, Farzad; Shojaei, Maziar; chouhdari, Arezoo (Student Research in Translational Medicine, 2022)
Background and aim: Stroke is recognized as the third leading cause of death in the world and is one of the most important causes of disability in adults. Hence, strategies that can be useful in improving condition of the patients suffering are constantly investigated. One of these strategies is the precise approach to transient ischemic attacks. Accordingly, this study was overall done to Determine clinical and brain Magnetic Resonance Imaging findings in patients with repeated stereotypical transient ischemic attack (TIA). Materials and Methods: 36 patients referred to Loghman-e-Hakim Hospital with symptoms of transient stereotypical ischemic attacks within the first 24 hours were enrolled in this study. Patients were followed up for a complete history at the time of entrance, and Brain CT was done. Cases with metabolic and toxic causes, existence of non-ischemic evidences in Brain CT, as well as prohibition of MRI, were excluded. The information was obtained by the various examinations of clinical presentation, underlying risk factors, as well as the history of medication, and it was entered in a data collection form. MRI (Brain and cervical MRA & Brain MRI) was performed for patients up to 72 hours. EEG was also done on patients with symptoms such as paresthesia or loss of consciousness, or patients suspected of seizure. Finally, the neurologist made the final diagnosis and the data were analyzed by a statistical expert using SPSS version 24. Result: 36 patients were enrolled in this study. According to the studied clinical symptom, 23 patients (63.8%) had hemiparesis, 5 patients (13.9%) had hemiparesthesia, 20 patients (55.5%) had dysarthria and 23 patients (63.8%) had facial palsy. among the 36 patients, 20 (55.5%) cases had DWI infarct that 14 (38.8%) cases were lacunar infarct and 6 (16.6%) cases were large infarct. among the 20 patients with infarct, the lacunar infarct of 12 (33.3%) cases were subcortical and 8 (22.2%) cases were cortical. Also, based on investigation of the artery stenosis, 18 patients (50%) had artery stenosis among which, 7 patients (19.4%) had stenosis of small vessels and 11 patients (30.6%) had stenosis of large vessels. According to the results of this study, there is a significant relationship between artery stenosis and infarct in DWI (P = 0.007). In addition, there was no significant difference between infarct size and the size of constricted arteries, in terms of DWI (P = 0.1). Conclusion: Most patients with repeated stereotypical TIA have infarct in DWI a thrombotic cause, and anticoagulant drug can be replaced by anticoagulants.